Pendampingan Pengembangan Lifeskill Santri Dengan Memanfaatkan Barang Bekas Di Pondok Pesantren Putra-Putri Miftahul Mubtadiin An-Nur Krempyang Nganjuk - Toha Ma'sum; M. Munir (LP3M STAI Darussalam Krempyang Nganjuk, 2020)
The Miftahul Mubtadiin An-Nur Islamic Boarding School is one of the Islamic boarding schools in Nganjuk Regency which is on Jalan KH. Wahid Hasim Krempyang Tanjunganom Nganjuk. This pesantren has sufficient human resources to develop its abilities in the field of skills of students. On the other hand, like the problems of society and the community in general, garbage or used goods is a problem in itself for Islamic boarding schools. Through mentoring activities carried out by service lecturers of STAI Darussalam, using the ABCD (Asset Baset Community Development) method, a mentoring program was carried out in the form of a workshop whose main focus was to improve the skills of students and find alternative solutions to minimize used goods or waste. With this method, activities are carried out well, get responses from assisted partners and have a positive impact on the students who become participants. And as a form of response, follow-up plans were implemented to develop the program